Microbial Populations in Deep Sea Water and Fish of South East Arabian Sea with Special Emphasis on Escherichia coli & Coliphages - B., Madhusudana Rao; P.K., Surendran (Fishery Technology, 2025)
Deep sea fish, deep sea surface water (DSW) and deep sea water from 200m depth (DSW2()0) and littoral sea water (LSW) of the Arabian Sea (8-130N Latitude, 74-760E Longitude) were analyzed for faecal indicators. E.coii could not be detected in DSW200. However, two deep-sea fish, Psenopsis cynea and Heterocarpus woodmasoni had low levels of E.coii, 0.3 MPN/ g and 0.7 MPN/g, respectively, at the time of harvest. E.coii strains isolated from deep sea environment have been found to be indistinguishable from terrestrial forms, either morphologically or biochemically. DSW had almost equal proportions of Gram -ve (22%) and Gram +ve (20%) bacteria whereas DSW200 had a high percentage of Gram +ve (46%) bacteria. In deep-sea fish. Gram -ve were almost double of Gram +ve bacteria. Pseudomonas was the predominant bacterial genus in deep-sea water samples whereas Vibrio was preponderant in deep-sea fish. DSW200, had significant proportions of Arthrobacter (24%) and filamentous bacteria (17%). Yeasts were detected only in deep-sea fish samples. LSW collected from a location 15 nautical miles off Quilon had high levels of faecal pollution. In LSW predominant Gram +ve bacterial genus was Micrococcus (16%) wheres Pseudomonas (13%) and Enterobacteriaceae (10%) were the prominent Gram -ve groups. E.coli and coliphages could not be detected in deep-sea waters. A few deep-sea fish at the time of harvest showed low levels of faecal pollution and were within the stipulated limits. The study showed that high count of E.coli and coliphages in deep-sea fish procured from landing centres is not due to polluted deep-sea fish or polluted deep-sea waters.